Traumatisms of the duodenum.: Clinico-Pathological aspects. - Estrugo, Roberto (Cirugía del Uruguay, 1989)
Traumatisms of the duodenum are not frequent (3-5%) among abdominal traumatisms, but are steadily increasing.